The Antiviral Potential of AdipoRon, an Adiponectin Receptor Agonist, Reveals the Ability of Zika Virus to Deregulate Adiponectin Receptor Expression - Daed El Safadi; Grégorie Lebeau; Jonathan Turpin; Christian Lefebvre d’Hellencourt; Nicolas Diotel; Wildriss Viranaicken; Pascale Krejbich-Trotot (Viruses, 2023)
Zika virus (ZIKV) is a pathogenic member of the flavivirus family, with several unique characteristics. Unlike any other arbovirus, ZIKV can be transmitted sexually and maternally, and thus produce congenital syndromes (CZS) due to its neurotropism. This challenges the search for safe active molecules that can protect pregnant women and their fetuses. In this context, and in the absence of any existing treatment, it seemed worthwhile to test whether the known cytoprotective properties of adiponectin and its pharmacological analog, AdipoRon, could influence the outcome of ZIKV infection. We showed that both AdipoRon and adiponectin could significantly reduce the in vitro infection of A549 epithelial cells, a well-known cell model for flavivirus infection studies. This effect was particularly observed when a pre-treatment was carried out. Conversely, ZIKV revealed an ability to downregulate adiponectin receptor expression and thereby limit adiponectin signaling.